Community Self-Efficacy of Coronary Heart Disease Based on Characteristic Risk Factors - Eka Afrima Sari; Seizi Prista Sari; Sri Hartati Pratiwi (Faculty of Nursing, Universitas Jember, 2018)
Coronary heart disease is one of the main causes of mortality rate in the world. This disease is affected by several risk factors. People who have high or moderate risk factors for coronary heart disease should have good preventive behavior, but this also requires a good level of self-efficacy as well, so that the expected behavior can be performed. This study aimed to determine the level of community self-efficacy of coronary heart disease based on characteristic risk factors. This research used a descriptive quantitative approach. Participant consisted of 70 people in Desa Limusgede, West Java, Indonesia acquired through a non-probability technique of purposive sampling. Self-efficacy was measured using a self-efficacy questionnaire (validity value in the range of 0.484 to 0.773 and reliability value 0.862) while risk factor data were determined by age, body mass index, blood pressure, smoking behavior, diabetes mellitus, and physical activity which were referenced by Jakarta Cardiovascular Score. Data were analyzed using median and frequency distribution. The results showed that median (minimum-maximum score) of self-efficacy is 26.00 (11-41), most of the respondent (62.86%) had high self-efficacy of coronary heart disease and more than a half respondent (47.14%) had moderate and high-risk factors for cardiovascular disease. Further, almost half the respondent who had high self-efficacy also had moderate and high-risk factors for cardiovascular disease. So, the health professional must concern in activities to decrease the level of cardiovascular risk factors, such as health education, health promotion, and disease prevention.